Investigating the psychological effects of home quarantine during the early peaks of the COVID-19 pandemic: a survey from Iran. (11th November 2022) - Nahidi, Mahsa; Ghalandarzadeh, Mojtaba; Sinichi, Farideh; Sahebzadeh, Narjes; Eslami, Saeid; Reihani, Hamidreza; Emadzadeh, Maryam; Fayyazi Bordbar, Mohammad Reza
Abstract : We assessed psychological symptoms among individuals who were quarantined during early coronavirus disease 2019 (COVID-19) peaks. This cross-sectional study was performed during April–October 2020 in Iran. We surveyed 100 individuals with COVID-19 patients in their families and 100 others with health conditions associated with a higher risk of developing critical forms of COVID-19 infection, who have completed at least 14 days of home quarantine. Validated Persian versions of the 21-item Depression, Anxiety, and Stress and 22-item Impact of Event Scale-Revised were used to measure the symptoms of depression, anxiety, stress and distress. The rates of stress, anxiety, depression and quarantine-related distress were 46.5, 48.5, 57.0 and 80.5%, respectively; however, they were not significantly different between the contact and no-contact groups. Female sex and being unemployed were significantly associated with quarantine-related distress, P = 0.007 and P = 0.018, respectively. Independent risk factors for anxiety were a history of medical comorbidity ( P = 0.025) and contact with COVID-19 patients ( P = 0.007). Findings show high prevalence rates of psychological symptoms among quarantined individuals, regardless of whether they had contact with COVID-19 patients or not. Female sex and unemployment were risk factors for quarantine-related distress.